Upaya Peningkatan Aktivitas Belajar Siswa Melalui Model Pembelajaran Kooperatif Tipe Make A Match - Letriani, Ni Kadek Okta; Tripalupi, Lulup Endah (Jurnal Pendidikan Ekonomi Undiksha, 2021)
This study is different from the problems in the twelfth category C OTKP (Otomatisasi Tata Kelola Perkantoran) SMK Negeri 1 Singaraja, whose student learning activities are still relatively low. In order to overcome these problems, the application in type matching of cooperative learning models is studied. The purpose of this study is to determine the increase in learning activities of middle school students in the XII C OTKP SMK Negeri 1 Singaraja category by applying cooperative learning model type matching to the second basic ability of entrepreneurship subjects. This study used the "Classroom Action Research" design. Use observation methods and documents to collect data, and analyze the data through simple percentage statistical analysis. The results show that the average learning integrity obtained by the students in the first cycle of learning activities is 64.05%, and the average learning integrity obtained in the second cycle is 84.08%.Research results prove that learning activity can increase after applying Cooperative Learning Model Type Make A Match in class XII C OTKP SMK Negeri 1 Singaraja.